Examining the association of elevated initial serum lactate with mortality and morbidity in trauma patients: a retrospective study - Pablo Rodríguez-Ortiz; Kyara Berríos-Toledo; Ediel O. Ramos-Meléndez; Lourdes Guerrios-Rivera (International Journal of Emergency Medicine)
Abstract Background Elevated initial serum lactate (iSL) levels are frequently employed to assess trauma severity, but their predictive value for mortality and morbidity remains inconsistent. We evaluated the association of iSL with mortality and morbidity at Puerto Rico Trauma Hospital (PRTH). Methods This IRB-approved retrospective study included trauma patients ≥ 18 years with iSL measured within the first 48 h of admission to PRTH (July 2014-June 2019). Patients were classified as normal (4.5–19.8 mg/dL) or elevated (≥ 19.9 mg/dL) iSL levels. Group comparisons were conducted using t-tests, Wilcoxon rank-sum tests, Pearson’s chi-squared, or Fisher’s exact tests. Associations were evaluated with regression and ROC analyses. Results Among 536 patients, 54.3% had elevated iSL levels. Initially, elevated iSL was associated with in-hospital mortality (OR: 2.18, 95%CI: 1.36–3.51, p < 0.001), traumatic intensive care unit (TICU) admission (OR: 2.06, 95%CI: 1.46–2.92, p < 0.001), and need for mechanical ventilation (MV) (OR: 2.80, 95%CI: 1.97–3.98, p < 0.001). However, adjusted analyses showed no significant associations (Mortality-AOR: 1.72, 95%CI: 0.97–3.04, p = 0.06; TICU-AOR: 1.11, 95%CI: 0.71–1.75, p = 0.65; MV-AOR: 1.49, 95%CI: 0.89–2.49, p = 0.13). Both iSL (AUC: 0.59, 95%CI: 0.54–0.64) and ISS (AUC: 0.59, 95%CI: 0.54–0.64) demonstrated limited ability to predict mortality, with no statistically significant difference between them (p > 0.99). Patients with elevated iSL experienced prolonged hospital and TICU stays and severe injuries. Conclusions Elevated iSL levels may not independently predict mortality, TICU admission, or the need for MV in trauma patients. However, their rapid availability supports their use alongside other clinical markers to guide trauma care decision-making and improve trauma outcomes.